How can patient-held lists of medication enhance patient safety? A mixed-methods study with a focus on user experience - Garfield,S; Furniss,D; Husson,F; Etkind,M; Williams,M; Norton,J; Ogunleye,D; Jubraj,B; Lakhdari,H; Franklin,BD (BMJ Quality & Safety, 2020)
Background Patients often carry medication lists to mitigate information loss across healthcare settings. We aimed to identify mechanisms by which these lists could be used to support safety, key supporting features, and barriers and facilitators to their use.Methods We used a mixed-methods design comprising two focus groups with patients and carers, 16 semistructured interviews with healthcare professionals, 60 semistructured interviews with people carrying medication lists, a quantitative features analysis of tools available for patients to record their medicines and usability testing of four tools. Findings were triangulated using thematic analysis. Distributed cognition for teamwork models were used as sensitising concepts.Results We identified a wide range of mechanisms through which carrying medication lists can improve medication safety. These included improving the accuracy of medicines reconciliation, allowing identification of potential drug interactions, facilitating communication about medicines, acting as an aide-mémoire to patients during appointments, allowing patients to check their medicines for errors and reminding patients to take and reorder their medicines. Different tools for recording medicines met different needs. Of 103 tools examined, none met the core needs of all users. A key barrier to use was lack of awareness by patients and carers that healthcare information systems can be fragmented, a key facilitator was encouragement from healthcare professionals.Conclusion Our findings suggest that patients and healthcare professionals perceive patient-held medication lists to have a wide variety of benefits. Interventions are needed to raise awareness of the potential role of these lists in enhancing patient safety. Such interventions should empower patients and carers to identify a method that suits them best from a range of options and avoid a ‘one size fits all’ approach.